Faecal calprotectin and rectal histological inflammatory markers in cystic fibrosis: a single-centre study. Issue 1 (29th April 2022) - Roda, Juliana; Maia, Carla; Almeida, Susana; Oliveira, Rui Caetano; Ferreira, Ricardo; Oliveira, Guiomar
Abstract : Objective: To analyse the association of faecal calprotectin with the genetic and clinical characteristics of paediatric patients with cystic fibrosis (PwCF). In a subset of these patients, we aimed to associate histological inflammatory features of rectal mucosa to faecal calprotectin levels. Methods: In a prospective study, faecal calprotectin levels were collected in all 23 PwCF attending our paediatric centre, together with demographic and clinical data. Associations between faecal calprotectin and clinical features were determined. In 11 of these patients, endoscopic rectal biopsies were obtained and the association between faecal calprotectin and histological inflammatory markers was analysed. Statistical analyses included Spearman's correlation coefficient, Mann-Whitney U test and Fisher's exact test. Sensitivity and specificity was calculated. Results: Median age of PwCF was 12 years, 19 had pancreatic insufficiency (PI) (19/23). Seventeen (17/23) had elevated faecal calprotectin, and the median value was 88 µg/g (IQR=178 µg/g). Higher faecal calprotectin levels were observed in the PI group (101 vs 30 µg/g, p=0.027). No significant correlation between elevated faecal calprotectin level and body mass index z-score was found. Five patients (22%) reported abdominal pain, three (13%) complained of diarrhoea and three (13%) had constipation, but these symptoms were not associated with elevated faecal calprotectin. Unspecific focal rectal inflammation was found in four patients (4/11). An association between rectal mucosa inflammation and elevated faecal calprotectin was found (p=0.015). Sensitivity was 100% and specificity was 86%. Conclusions: In our PwCF, elevated faecal calprotectin was frequent, particularly if PI, and it was not related to gastrointestinal symptoms or malnutrition. Elevated faecal calprotectin was present in patients with histological evidence of rectal inflammation. Faecal calprotectin may be an indicator of asymptomatic rectal inflammation in PwCF.